3‐Acrylamidophenylboronic Acid‐Modified Hydrogel Film Attached to a Gold Nanosphere Array to Detect Hydrofluoric Acid with Good Selectivity and Recyclability. Issue 2 (10th October 2017) - Men, Dandan; Hang, Lifeng; Zhang, Honghua; Zhang, Xiaomin; Lyu, Xianjun; Cai, Weiping; Li, Yue
Abstract: A novel hydrofluoric acid sensor was prepared by attaching a two‐dimensional (2D) gold nanosphere array onto the surface of a poly(acrylamide‐co‐3‐acrylamidophenylboronic acid) P(AAm‐co‐APBA) hydrogel film. The volume of the hydrogel film swelled with increasing concentration of hydrofluoric acid due to the formation of borofluoride anions between hydrofluoric acid and phenylboronic acid group, resulting in a red shift of diffraction wavelength. The concentration of hydrofluoric acid was determined through monitoring the wavelength of the diffraction spectra. Additionally, this hydrofluoric acid sensor exhibited good sensitivity, selectivity and recyclability. Moreover, this method may be applied to detect various substances and could be widely used in diverse areas such as biochemical sensors, environmental monitoring, and food analysis by selecting an appropriate recognition agent attached to the hydrogel carrier. Abstract : A HF acid sensor with good recyclability and selectivity was fabricated by embedding a 2D Au nanosphere array in a 3‐acrylamidophenylboronic acid‐functionalized hydrogel film. The volume of hydrogel film swelled with increasing concentration of HF acid, resulting in a red shift of the diffraction wavelength. The concentration of HF acid could be detected by monitoring the wavelength of the diffraction spectra.